Exploring life phenomena with statistical mechanics of molecular liquids - Hirata, Fumio ([Place of publication not identified] : CRC Press, 2020)
In a living body, a variety of molecules are working in a concerted manner to maintain its life, and to carry forward the genetic information from generation to generation. A key word to understand such processes is "water," which plays an essential role in life phenomena. This book sheds light on life phenomena, which are woven by biomolecules as warp and water as weft, by means of statistical mechanics of molecular liquids, the RISM and 3D-RISM theories, both in equilibrium and non-equilibrium. A considerable number of pages are devoted to basics of mathematics and physics, so that students who have not majored in physics may be able to study the book by themselves. The book will also be helpful to those scientists seeking better tools for the computer-aided-drug-discovery. Explains basics of the statistical mechanics of molecular liquids, or RISM and 3D-RISM theories, and its application to water. Provides outline of the generalized Langevin theory and the linear response theory, and its application to dynamics of water. Applies the theories to functions of biomolecular systems. Applies the theories to the computer aided drug design. Provides a perspective for future development of the method.
General Introduction. Fundamentals: Basic Concepts Related to Statistical Mechanics. Statistical Mechanics of Liquid and Solutions. Dynamics of Liquids and Solutions. Theory of Biomolecular Solvation and Molecular Recognition. Structural Fluctuation and Dynamics of Protein in Aqueous Solutions. Applications of the Theories to In-silico Drug Discovery. References. Epilogue.
OCLC-licensed vendor bibliographic record.
Keywords: Biomolecules; Statistical mechanics; Biomolecules -- Mathematics; Protein-protein interactions